2022
DOI: 10.1007/s40653-022-00449-2
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence, Patterns and Correlates of Childhood Trauma Exposure in a Nationally Representative Sample of Young People in Northern Ireland

Abstract: Purpose Childhood trauma (CT) exposure is common, with many young people affected by multiple co-occurring traumas. Methods Participants were a representative sample of 11–19-year-olds (n = 1293), who participated in the largest ever representative survey of youth mental health in Northern Ireland (NI) – the NI Youth Wellbeing Prevalence Survey 2020. This study used latent class analysis (LCA) to identify typologies that were most representative of trauma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 83 publications
2
1
0
Order By: Relevance
“…Consistent with prior studies conducted in Western nations (e.g., Karsberg et al, 2014;O'Donnell et al, 2017;Petersen et al, 2010;Redican et al, 2022;Shevlin & Elklit, 2008), the smallest class identified for both samples was characterized by high levels of exposure to many PTEs. These included severe childhood neglect, serious accident, lifethreatening situations, sexual trauma, and exposure to threats of violence and bullying for the Indian sample and all PTEs for the Malaysian sample.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Consistent with prior studies conducted in Western nations (e.g., Karsberg et al, 2014;O'Donnell et al, 2017;Petersen et al, 2010;Redican et al, 2022;Shevlin & Elklit, 2008), the smallest class identified for both samples was characterized by high levels of exposure to many PTEs. These included severe childhood neglect, serious accident, lifethreatening situations, sexual trauma, and exposure to threats of violence and bullying for the Indian sample and all PTEs for the Malaysian sample.…”
Section: Discussionsupporting
confidence: 86%
“…Consistent with prior studies (e.g., Karsberg et al, 2014;Petersen et al, 2010;Redican et al, 2022;Shevlin & Elklit, 2008), the second largest class was characterized by moderate levels of exposure to a small collection of PTEs. Events that were heavily endorsed in this class for both samples included death of someone close and threats of violence or bullying, baring semblance to the 'physical assault, threats of violence, and bullying class' identified by Petersen et al (2010) in their sample of Faroese adolescents and the 'physical assault, threats of violence, neglect, and humiliation or persecution from others class' identified by Karsberg et al (2014) in their sample of Greenlandic adolescents.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation